Building Communities for All Ages: Lessons Learned from an Intergenerational Community‐building Initiative. (January 2014) - Brown, Corita; Henkin, Nancy
ABSTRACT The outcomes of the Communities for All Ages initiative suggest that a lifespan approach to community building helps foster social capital across diverse populations and increase public will among younger generations to address ageing issues. This is crucial as global ageing and immigration trends impact age relations and resource distribution. Although demographic changes create many opportunities for connection and collaboration, decisions about public investments, land use planning and service delivery are becoming increasingly complex. To build support for older adults, we need strategies that foster 'shared fate' across age, race and ethnicity and encourage alliances rather than competition. Copyright © 2013 John Wiley & Sons, Ltd.